2005
DOI: 10.4049/jimmunol.175.12.7981
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized β-Catenin Extends Thymocyte Survival by Up-Regulating Bcl-xL

Abstract: CD4+CD8+ double-positive (DP) thymocytes, which are extremely sensitive to apoptosis, specifically up-regulate Bcl-xL to extend their lifespan. Deletion of the Bcl-xL gene leads to premature apoptosis of the thymocytes. In this study, we show that stabilization of β-catenin, a critical coactivator for T cell factor (TCF), enhances DP thymocyte survival via up-regulating Bcl-xL. Spontaneous or glucocorticoid-induced thymocyte apoptosis was associated with reduced levels of β-catenin and Bcl-xL. Transgenic expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
91
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 40 publications
9
91
0
1
Order By: Relevance
“…Previously we have shown that transgenic expression of stabilized ␤-catenin (␤-cat Tg ) protects CD4 ϩ CD8 ϩ thymocytes from spontaneous apoptosis by specifically up-regulating Bcl-x L in this subset of thymocytes (16). These results were consistent with the role of TCF-1 in the survival of the CD4 ϩ CD8 ϩ thymocytes (17,18).…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Previously we have shown that transgenic expression of stabilized ␤-catenin (␤-cat Tg ) protects CD4 ϩ CD8 ϩ thymocytes from spontaneous apoptosis by specifically up-regulating Bcl-x L in this subset of thymocytes (16). These results were consistent with the role of TCF-1 in the survival of the CD4 ϩ CD8 ϩ thymocytes (17,18).…”
supporting
confidence: 79%
“…tg mice used in this study have been previously described (16). Mice were housed at the specific pathogen-free animal facility of the Biological Resource Laboratory of the University of Illinois at Chicago, following university guidelines.…”
Section: ␤-Catmentioning
confidence: 99%
See 1 more Smart Citation
“…4D). β-catenin has been shown to directly activate the expression of Bcl-xL (45,47,48), and we found that Bcl-xL is a critical downstream mediator of the addiction to β-catenin in MYC-induced lymphomas. The phenotypic consequences of β-catenin inhibition may be explained by an "oncogenic shock" model, in which the rapid loss of survival cues such as Bcl-xL and the persistence of proapoptotic signaling results in an imbalance that favors cell death (49).…”
Section: Discussionmentioning
confidence: 76%
“…This result confirmed a critical role of CnA␤ in T cell activation. To determine whether cell death contributed to the significantly reduced [ 3 H]thymidine incorporation by CnA␤ Ϫ/Ϫ T cells, we performed a apoptosis assay using annexin V and 7-aminoactinomycin D as described previously (16,23,24). We first analyzed apoptosis of the CD4 ϩ T cells obtained from WT and (Fig.…”
Section: ϫ/ϫ T Cells Undergo Accelerated Spontaneous Apoptosismentioning
confidence: 99%